Low-dose IL-2 treatment confers anti-inflammatory effect against subarachnoid hemorrhage in mice - Jia Liu; Biao Qi; Yanrong Ye; Yun Shen; Yufu Lin; Yabo Chen; Shan Ding; Jun Ma; Shaozhuang Chen (Heliyon, 2024)
Objective: Subarachnoid hemorrhage (SAH) was a stroke with high occurrence and mortality. At the early stage, SAH patients have severe cerebral injury which is contributed by inflammation. In this study, we aimed to explore the anti-inflammation effect of low-dose IL-2 in SAH mice. Methods: The 12-week-old C57BL/6J male mice were conducted with SAH surgery (Internal carotid artery puncture method). Different dose of IL-2 was injected intraperitoneally for 1 h, 1 day, and 2 days after SAH. Single-cell suspension and flow cytometry were used for the test of regulatory T (Treg) cells. Immunofluorescence staining was used to investigate the phenotypic polarization of microglia and inflammation response around neurons. Enzyme-Linked Immuno-sorbent Assay (ELISA) was applied to detect the level of pro-inflammatory factors. Results: Low-dose IL-2 could enrich the Treg cells and drive the microglia polarizing to M2. The level of pro-inflammatory factors, IL-1α, IL-6, and TNF-α decreased in the low-dose IL-2 group. The inflammation response around neurons was attenuated. Low-dose IL-2 could increase the number of Treg cells, which could exert a neuroprotective effect against inflammation after SAH. Conclusion: Low-dose IL-2 had the potential to be an effective clinical method to inhibit inflammation after SAH.